2010
DOI: 10.1007/s11908-010-0144-x
|View full text |Cite
|
Sign up to set email alerts
|

The Rapidly Evolving Research on Vitamin D Among HIV-Infected Populations

Abstract: With ongoing improvement in antiretroviral therapy, mortality among HIV-infected persons has dramatically decreased. For HIV-infected persons who remain engaged in care on suppressive therapy, life expectancy approaches that of the general population. Additionally, we have seen increases in comorbidities traditionally associated with aging: diabetes, hypertension, dyslipidemia, ischemic heart disease, and osteoporosis. Vitamin D deficiency has also been identified as a highly prevalent entity among HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 98 publications
(75 reference statements)
4
27
1
Order By: Relevance
“…9,10,24,29,31,35,37,38,40,45,51 Such findings are supported by the pharmacology of these compounds, since it is well established that some of them may affect the metabolism of vitamin D (eg, via cytochrome P450 enzymes). 19 Similarly, the potential protective effect against These findings are not surprising since similar findings have been reported also in HIV-uninfected individuals, [67][68][69][70] further supporting the role of hypovitaminosis D in the pathogenesis of several chronic diseases. [15][16][17][18] The most important and striking findings are those that related low vitamin D concentrations to the progression of HIV infection.…”
Section: Vitamin D Deficiencysupporting
confidence: 62%
See 2 more Smart Citations
“…9,10,24,29,31,35,37,38,40,45,51 Such findings are supported by the pharmacology of these compounds, since it is well established that some of them may affect the metabolism of vitamin D (eg, via cytochrome P450 enzymes). 19 Similarly, the potential protective effect against These findings are not surprising since similar findings have been reported also in HIV-uninfected individuals, [67][68][69][70] further supporting the role of hypovitaminosis D in the pathogenesis of several chronic diseases. [15][16][17][18] The most important and striking findings are those that related low vitamin D concentrations to the progression of HIV infection.…”
Section: Vitamin D Deficiencysupporting
confidence: 62%
“…The last criterion was chosen because it is well established that the concentration of 25OHD is the best indicator of vitamin D status, and because most of the data on the relationship between vitamin D insufficiency/ deficiency and adverse health outcomes are based on 25OHD concentration measurements. [11][12][13][14][15][16][17][18][19] A single author (AG) reviewed all identified studies for eligibility, definitive inclusion/exclusion, and for data collection.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis would not have captured the impact of changes in 25(OH)D associated with ART initiation or nutritional status that may have occurred during the course of the study. 21 The small sample population and event number may have limited our power to detect significant differences in outcomes (i.e., survival, clinical response, receipt of adjunctive therapy, development of KS-IRIS). Receipt of chemotherapy or radiation therapy was affected by availability.…”
Section: Discussionmentioning
confidence: 99%
“…21 In HIV infection specifically, our understanding of the effect of vitamin D on immune function is rapidly evolving but far from clear. 22 Vitamin D deficiency was associated with lower CD4 count in one study of postmenopausal women, 23 but other studies have not confirmed the association. 24,25 Women with HIV were less likely to have BV, but among HIV-infected women, those with a lower CD4 count were more likely to have BV.…”
Section: Discussionmentioning
confidence: 96%